The regulatory process of the Visual and Technological Education teachers' activity: analysis of the impact of the 2012 Curricular Restructure in Portugal - Cláudia Pereira; Marta Santos (Universidade do Porto, 2017)
This paper aims at exploring a case study of a group of teachers of the 2 nd Cycle of Basic Education, for pupils aged 10 and 11 according to the Portuguese Education System, who belong to the disciplinary group of Visual and Technological Education. The analysis is twofold: it focuses on the one hand on understanding the changes in the work activity and the constraints that resulted from changes in education implemented at national level; and on the other hand on the identification of regulatory strategies developed by the teachers. Based on the fieldwork (individual interviews, activity analysis, documentary analysis) there is evidence of variations and constraints, as a result from the changes, both in the teachers' activity (e.g. increase in the workload) and in their health (e.g. tiredness, anxiety, disappointment). In order to face the constraints they were experiencing, the teachers developed individual, but also group regulatory strategies, demonstrating the protective and supportive effect the group had in the continuity of the work and in the preservation of these teachers' health.